Power and Responsibility: Conversations with Contributors. - Van Belle, Guy (Leonardo Music Journal, 1999)
Discusses various topics related to computer music. Electronic musical composition; Interactive software design for musicians; Sources of sound materials; Web sites distributing sound files, tools and programs.